Disulfiram-Mitigating Unintended Effects - Martha M. Grout; Kenneth B. Mitchell (MDPI AG, 2023)
Lyme disease caused by infection with a multitude of vector-borne organisms can sometimes be successfully treated in its very early stages. However, if diagnosis is delayed, this infection can become disseminated and, like another spirochetal infection syphilis, can affect multiple organ systems in the body, causing a wide variety of life-altering symptoms. Conventional antibiotic therapy may not be effective in eradicating the symptoms of the disease we know as Lyme disease. The recent literature has suggested that disulfiram (DSM) may be a potent drug in the armamentarium of physicians who treat chronic Lyme disease. The use of disulfiram in the treatment of Lyme disease started with a researcher who determined that DSM is bactericidal to spirochete. Encouraged by published case reports of apparent recovery from chronic Lyme disease, having prescribed DSM ourselves in the past for alcoholics who had a desire to stop drinking and prescribing it now for patients with chronic Lyme disease, we observed both predictable and potentially avoidable side effects not necessarily related to the ingestion of alcohol. We reviewed the published literature in PubMed and Google Scholar, using the following key words: Lyme Disease; Borrelia burgdorferi treatment; and disulfiram toxicity. This paper outlines the results of that research to help avoid some of the pitfalls inherent in this novel use of an old and established medication in the practice of clinical medicine.